OR 2.0 context-aware operating theaters, computer assisted robotic endoscopy, clinical image-based procedures, and skin image analysis : first International Workshop, OR 2.0 2018, 5th International Workshop, CARE 2018, 7th International Workshop, CLIP 2018, third International Workshop, ISIC 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16 and 20, 2018, Proceedings /: first International Workshop, OR 2.0 2018, 5th International Workshop, CARE 2018, 7th International Workshop, CLIP 2018, third International Workshop, ISIC 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16 and 20, 2018, Proceedings. (2018) - Unknown
No abstract available